ON A RECURSIVE METHODOLOGY FOR SEMI-ANALYTICAL SOLUTIONS OF SYMMETRIC AND UNSYMMETRIC LAMINATED THIN PLATES (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The present paper has as objective the introduction and analysis of a new procedure in order to derive semi-analytical solutions of symmetric and unsymmetrical laminated rectangular thin plates in a recursive manner. The methodology is based on three main characteristics: (a) decomposition of the differential operator into two or more components, (b) an infinite expansion of the differential equation solution and, (c) determination of each superposed solution by a relationship between the divided operators and previous solutions. The first expanded term concerns to the plate’s isotropic solution and, in each step, orthorhombic laminae influence is inserted. In order to approximate the solutions, the pb-2 Rayleigh-Ritz Method is used. Obtained solutions are discussed and compared to those found in the literature.